The effect of spermidine on autoimmunity and beta cell function in NOD mice - Ceren Karacay; Barbara Prietl; Clemens Harer; Barbara Ehall; Christoph W. Haudum; Kaddour Bounab; Joakim Franz; Tobias Eisenberg; Frank Madeo; Dagmar Kolb; Kerstin Hingerl; Markus Hausl; et al. (Scientific Reports, 2022)
Abstract Spermidine is a natural polyamine which was shown to prolong lifespan of organisms and to improve cardiac and cognitive function. Spermidine was also reported to reduce inflammation and modulate T-cells. Autophagy is one of the mechanisms that spermidine exerts its effect. Autophagy is vital for β-cell homeostasis and autophagy deficiency was reported to lead to exacerbated diabetes in mice. The effect of spermidine in type 1 diabetes pathogenesis remains to be elucidated. Therefore, we examined the effect of spermidine treatment in non-obese diabetic (NOD) mice, a mouse model for type 1 diabetes. NOD mice were given untreated or spermidine-treated water ad libitum from 4 weeks of age until diabetes onset or 35 weeks of age. We found that treatment with 10 mM spermidine led to higher diabetes incidence in NOD mice despite unchanged pancreatic insulitis. Spermidine modulated tissue polyamine levels and elevated signs of autophagy in pancreas. Spermidine led to increased proportion of pro-inflammatory T-cells in pancreatic lymph nodes (pLN) in diabetic mice. Spermidine elevated the proportion of regulatory T-cells in early onset mice, whereas it reduced the proportion of regulatory T-cells in late onset mice. In summary spermidine treatment led to higher diabetes incidence and elevated proportion of T-cells in pLN.